Educational seminar supervision and quality assurance through educational reports - Waska Warta; Ervin Aulia Rachman; Daris Yolanda Sari; Dita Humaeroh (Sean Institute, 2024)
Understanding supervision, quality assurance, and educational reports is essential for School Principals in organizing quality education. Therefore, a community service project is planned through an Education Seminar with the theme